Competitiveness analysis of the Malaysian cocoa industry - Jeffery, Farniza Shareen (2014)
The Malaysian cocoa industry has successfully transforming itself from major cocoa beans producer to a major producer of semi-finished cocoa products. Unfortunately, the declining trend in cocoa beans production has led to the dependence on imported cocoa beans which may expose Malaysian cocoa processors to great risk when there is a squeeze in world supply of cocoa beans. An increase in import transactions also requires the use of more foreign exchange, which could otherwise be used for the importation of other important commodities. This raised the question on the competitiveness of the Malaysian cocoa industry. Therefore, this study applies the value chain and competitiveness analysis in order to assess the competitiveness of the cocoa mid-stream and down-stream sector. It is important to examine whether the disadvantage position in the up-stream sector affects the competitiveness of the cocoa mid-stream and down-sector. The cocoa value chain is significant in providing clearer picture of the current operation of the cocoa industry in Malaysia and to identify the opportunity for upgrading in becoming the major producer of chocolate products. The value chain analysis requires chain mapping and impact assessment of the chain. The value chain analysis is computed by using the data collected from cocoa manufacturing survey and company’s annual financial statement with the reference year of 2011. The input-output flow in the chain reveals that the cocoa processors rely heavily on imported cocoa beans and the function of the cocoa farmers in the cocoa value chain is insignificant to the cocoa processors. The chain analysis also indicates that the cocoa mid-stream sector is more concentrated towards the export market. The cocoa down-stream sector is considered as an emerging sector in Malaysia with more concentration in the domestic market. However, this sector contributed more towards Malaysia’s GDP. Total value added worth of RM1.529 billion was created in 2011 with RM1.082 billion contributed by the cocoa down-stream sector and RM447 million by the cocoa mid-stream sector. Assessments on the competitiveness of the Malaysian cocoa industry were conducted on two perspective; ex-ante (potential) and ex-post (performance). The ex-ante competitiveness is measured by the comparative advantage analysis using the coefficients such as the Domestic Resource Cost (DRC), the Net Social Profit (NSP) and the Social Cost Benefit (SCB). The secondary data from the Department of Statistic’s Annual Survey on Manufacturing Industries was employed covering the period from 2000-2009. The result shows that the Malaysian cocoa processing and cocoa manufacturing sector has a comparative advantage due to efficiency in resource allocation. However, the productions of finished products save more foreign exchange. The factor that improves the comparative advantage position of the cocoa manufacturing sector is the decrease in traded and non-traded input cost. The cocoa processing sector is less competitive than the manufacturing sector. This is associated with the increase in traded input especially in raw material cost. The market share performance was analysed at sector and product levels using the coefficients such as the Revealed Comparative Advantage (RCA), Net Export Index (NEI) and the Relative Trade Advantage (RTA) indicators. Data from UNComtrade in the form of harmonized system (HS) code at 6 digits were collected covering the period of 2000 to 2011. The result proves that the up-stream sector of the cocoa industry has a competitive disadvantage position. The mid-stream sector or the cocoa processing industry is very competitive as the Malaysian grinders are able to expand and sustain their market shares in the international market. The down-stream sector of the cocoa industry is improving its competitive advantage position. The most competitive products for the Malaysian cocoa industry are the cocoa butter and cocoa powder. The value chain analysis, comparative advantage analysis and market share analysis conducted in this study shows that each sector in the cocoa value chain played a vital role in ensuring the competitiveness of the cocoa industry. The dependency on imported cocoa beans may expose Malaysian cocoa processors to any supply squeeze in the global cocoa market. The development of the cocoa manufacturing sector has also been very much dependent on the performance of the grindings sector in providing cost competitive raw material. Hence, this study recommends that the government should strongly promote and encourage the cocoa up-stream sector, promote economies of scale in the mid-stream sector and enhance the quality aspect in the cocoa down-stream sector.